1987
DOI: 10.1002/ijc.2910390623
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐tumor effects of interferon in mice injected with interferonsensitive and interferon‐resistant friend leukemia cells. VI. Adjuvant therapy after surgery in the inhibition of liver and spleen metastases

Abstract: Adult DBA/2 mice were injected s.c. with the highly malignant, interferon-resistant 3C18 line of Friend erythroleukemia cells (FLC). Eight or 9 days after established s.c. tumors had developed, the primary tumor was excised and mice were treated i.p. with either mouse interferon alpha/beta or a control preparation. At the time of surgery, mice already had tumor cells in the liver. All control-treated mice died in the ensuing 2 weeks with extensive tumor metastases in the liver and spleen. Interferon treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1988
1988
2007
2007

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Previous work showed that potent preparations of mouse interferon alp exerted an anti-metastatic effect when injected at the site of tumor implantation (Belardelli et al, 1983) or as adjuvant therapy after excision of established primary S.C. FLC tumors (Gresser et al, 1987). In the latter experiments, interferon therapy was effective even if initiated when tumor metastases were already present in the liver (Gresser er al., 1987).…”
Section: Mice After Intravenous Inoculation Of Friend Erythroleukemiamentioning
confidence: 96%
“…Previous work showed that potent preparations of mouse interferon alp exerted an anti-metastatic effect when injected at the site of tumor implantation (Belardelli et al, 1983) or as adjuvant therapy after excision of established primary S.C. FLC tumors (Gresser et al, 1987). In the latter experiments, interferon therapy was effective even if initiated when tumor metastases were already present in the liver (Gresser er al., 1987).…”
Section: Mice After Intravenous Inoculation Of Friend Erythroleukemiamentioning
confidence: 96%
“…Cure of metastatic malignancies can result when micrometastases are eliminated in patients at highest risk for recurrence after surgical removal of a primary tumour. effectiveness as a surgical adjuvant for murine tumours provided the rationale leading to pioneering clinical studies that suggested benefit of impure IFNα when given after surgery for osteosarcoma 217,218 . This surgical adjuvant approach was the basis for evalua tion of IFNα2 in patients at high risk for recurrence of melanoma.…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…In the model in which FLC are injected s.c., for example, mice died in the weeks following tumor injection, not of the large S.C. tumors but of overwhelming liver and spleen metastases (62). Eight days after S.C. inoculation of FLC tumor cells had already implanted and multiplied in the liver and spleen (65). Nevertheless, if interferon treatment is initiated at this time (8 days after tumor inoculation), a marked increase in survival time was observed and some of the mice were considered cured (65).…”
Section: -898103mentioning
confidence: 99%
“…Eight days after S.C. inoculation of FLC tumor cells had already implanted and multiplied in the liver and spleen (65). Nevertheless, if interferon treatment is initiated at this time (8 days after tumor inoculation), a marked increase in survival time was observed and some of the mice were considered cured (65). We extended these experiments and injected several million FLC i.v.…”
Section: -898103mentioning
confidence: 99%